Up‐regulation of HDACs, a harbinger of uraemic endothelial dysfunction, is prevented by defibrotide. Issue 2 (28th November 2019) - Palomo, Marta; Vera, Manel; Martin, Susana; Torramadé‐Moix, Sergi; Martinez‐Sanchez, Julia; Belen Moreno, Ana; Carreras, Enric; Escolar, Ginés; Cases, Aleix; Díaz‐Ricart, Maribel
Abstract: Endothelial dysfunction is an earlier contributor to the development of atherosclerosis in chronic kidney disease (CKD), in which the role of epigenetic triggers cannot be ruled out. Endothelial protective strategies, such as defibrotide (DF), may be useful in this scenario. We evaluated changes induced by CKD on endothelial cell proteome and explored the effect of DF and the mechanisms involved. Human umbilical cord vein endothelial cells were exposed to sera from healthy donors (n = 20) and patients with end‐stage renal disease on haemodialysis (n = 20). Differential protein expression was investigated by using a proteomic approach, Western blot and immunofluorescence. HDAC1 and HDAC2 overexpression was detected. Increased HDAC1 expression occurred at both cytoplasm and nucleus. These effects were dose‐dependently inhibited by DF. Both the HDACs inhibitor trichostatin A and DF prevented the up‐regulation of the endothelial dysfunction markers induced by the uraemic milieu: intercellular adhesion molecule‐1, surface Toll‐like receptor‐4, von Willebrand Factor and reactive oxygen species. Moreover, DF down‐regulated HDACs expression through the PI3/AKT signalling pathway. HDACs appear as key modulators of the CKD‐induced endothelial dysfunction as specific blockade by trichostatin A or by DF prevents endothelial dysfunction responses to the CKD insult. Moreover, DF exerts its endothelial protective effect by inhibiting HDAC up‐regulation likely through PI3K/AKT.